2017
DOI: 10.1139/apnm-2016-0497
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the health benefits of reduced-exertion high-intensity interval training (REHIT) and moderate-intensity walking in type 2 diabetes patients

Abstract: Background/Aim: Reduced-exertion high-intensity interval training (REHIT) is a genuinely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
89
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 49 publications
(61 reference statements)
8
89
2
5
Order By: Relevance
“…However, unlike our study's MICT+RT improvement of 4.6 mL/kg/min, prior studies have generally reported lower improvements for MICT ranging from 0.2 mL/kg/min (56) to 3.3 mL/kg/min (57). …”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…However, unlike our study's MICT+RT improvement of 4.6 mL/kg/min, prior studies have generally reported lower improvements for MICT ranging from 0.2 mL/kg/min (56) to 3.3 mL/kg/min (57). …”
Section: Discussioncontrasting
confidence: 98%
“…The improvements in aerobic capacity of our participants are on parity with prior reported improvements in VO 2 max that ranged from 1.9 mL/kg/min (56) to 6.1 mL/kg/min (57) for HIIT. However, unlike our study's MICT+RT improvement of 4.6 mL/kg/min, prior studies have generally reported lower improvements for MICT ranging from 0.2 mL/kg/min (56) to 3.3 mL/kg/min (57).…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, [12] investigate INT modality compared to AE training in 16 men with DM2. Participants completed a reduced-exertion high-intensity interval training (REHIT) and moderate-intensity walking for 8 weeks with a 2-months wash-out period between interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither intervention significantly improved OGTT, glycemic control measured using continuous glucose monitors, blood lipid profile or body composition. Indicating that REHIT led to a higher aerobic fitness than walking, however, neither strategies were effective interventions for improving insulin sensitivity or glycemic control in DM2 patients in a shortterm period [12]. While, [13] examined the effect of a single session of cardio and resistance INT training in 35 participants with DM2 and control groups, which was composed of highly trained and untrained normoglycemic adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation